PENGARUH PENGGUNAAN STRATEGI GALLERY WALK TERHADAP PEMAHAMAN MEMBACA SISWA KELAS DUA DI SMP MUHAMMADIYAH 1 PEKANBARU - Nabila Jannati; Jismulatif Jismulatif (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
The research was aimed to find out the effect of gallery walk strategy toward reading comprehension of the second year students of SMP Muhammadiyah 1 Pekanbaru. The design of this research was quasi-experimental research with an experimental group and control group pre-test and post-test. These two groups were selected to be a sample by using cluster random sampling. The data were analyzed by using t-test formula. It was found that t-test score was 2.351 while the t-table was 2.001. Since t-test score was higher than t-table, it can be concluded that alternative hypothesis was accepted. It means that there is a significant effect of gallery walk strategy on reading comprehension of the second year students of SMP Muhammadiyah 1 Pekanbaru.